Railing Against the Company Union: The State, Union Substitution, and the Montréal Tramways Strike of 1943 - Tucker, Sean; Thorn, Brian (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2006)
Abstract At the height of world war II labour unrest, Montréal tramway workers, themajority of whom were French Canadian, struck over recognition of their Canadian Congress of Labour-affiliated union over two entrenched rival unions. The strike, which threatened critical wartime production in Canada’s largest industrial centre, illustrates how multi-union workplaces were a source of wartime industrial disorder. Circumstances related to the strike tested the capacity of the federal government to respond in a way which was compatible with Prime Minister King’s broader goals of industrial stability and national unity. King’s inaction on labour law reform at this time led key cabinet ministers to pursue criminal charges against the parties involved in the tramway strike. However, legal proceedings were obverted after King intervened on a recommendation from Carl Goldenberg, who had successfully conciliated the strike. Concurrent to these events was the announcement of a wide-ranging public inquiry into national labour unrest, which eventually led to the adoption of a new labour code (pc 1003). The new federal labour law adopted provisions similar to those in the us Wagner Act, which severely limited union substitution, subjugating worker free choice and collective self-determination to the goals of capital and the state.